2016
DOI: 10.1371/journal.pone.0158886
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Maternal Plasma Adiponectin from Late Pregnancy to the Postpartum Period According to the Mode of Delivery: Results from a Prospective Cohort in Rio de Janeiro, Brazil

Abstract: IntroductionMaternal plasma adiponectin is inversely related to insulin resistance, atherosclerosis and child health. However, little is known about its concentrations in the perinatal period, especially according to mode of delivery. Our aim is to evaluate the association between mode of delivery and changes in maternal plasma adiponectin from 3rd trimester of pregnancy to 30–45 days postpartum.MethodsA cohort was recruited in Rio de Janeiro, Brazil, with four waves of follow-up: 5-13th, 22-26th, 30-36th gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Nevertheless, the mode of delivery did not have statistical effects on umbilical cord blood adiponectin concentrations. A similar result was obtained in Brazil, where the adiponectin concentrations were reported higher in the vaginal delivery group [18].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, the mode of delivery did not have statistical effects on umbilical cord blood adiponectin concentrations. A similar result was obtained in Brazil, where the adiponectin concentrations were reported higher in the vaginal delivery group [18].…”
Section: Discussionsupporting
confidence: 85%
“…In recent years, the rate of cesarean section (C-section) deliveries is suggestive of an increasing trend worldwide [17]. C-section as a surgical procedure is usually extremely stressful experience which can lead to an inflammatory situation and change the concentration of adiponectin [18]. The results of a systematic review revealed that C-section is associated with an increased risk of type-1 diabetes, asthma and metabolic syndrome as long-term outcomes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Koren et al demonstrated that the progesterone concentration could influence the relative abundance of Bifidobacterium in the maternal gut microbiota [95]. Further, Rebelo et al identified differences in the adiponectin concentration according to the mode of birth, with CS delivery being associated with a lower adiponectin concentration than VAG delivery at 30-45 days post-partum, which was likely mediated by the long-term inflammation associated with the CS procedure [96].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cesarean section is associated with an increased risk of asthma, allergies, type 2 diabetes, celiac disease [9] and obesity risks during adulthood [10]. Both cesarean sections and vaginal delivery are known as an inflammatory processes which can lead to changes in the level of anti-inflammatory adipokines [11,12].…”
Section: Introductionmentioning
confidence: 99%